2000
DOI: 10.1111/j.1530-0277.2000.tb04585.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Nicotinic Receptors in Alcohol Self‐Administration

Abstract: The stimulation of alcohol intake induced by nicotine treatment and the suppression of alcohol intake induced by mecamylamine provide evidence for the involvement of nicotinic receptors in alcohol consumption and/or self-administration. The failure of DHbetaE to reduce alcohol consumption, however, suggests that ethanol-nicotine interaction is mediated by other nicotinic receptor subtypes rather than alpha4beta2 receptor subtype, or that mecamylamine acts through a nonnicotinic mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
100
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(115 citation statements)
references
References 41 publications
9
100
1
3
Order By: Relevance
“…The ␣4␤2 nAChRs do not seem to have a major role in modulating acute responses to ethanol because the ␣4␤2 nAChR antagonist, dihydro-␤-erythroidine, did not decrease voluntary ethanol consumption in rats (22) and had no effect on ethanolinduced locomotor activity or ethanol-induced dopamine release in mice or rats (45,46). In contrast, in our work the animals were exposed to ethanol from 2 to 5 months before the varenicline treatment.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…The ␣4␤2 nAChRs do not seem to have a major role in modulating acute responses to ethanol because the ␣4␤2 nAChR antagonist, dihydro-␤-erythroidine, did not decrease voluntary ethanol consumption in rats (22) and had no effect on ethanolinduced locomotor activity or ethanol-induced dopamine release in mice or rats (45,46). In contrast, in our work the animals were exposed to ethanol from 2 to 5 months before the varenicline treatment.…”
Section: Discussioncontrasting
confidence: 43%
“…The nAChRs are well characterized ligandgated ion channels that, in addition to mediating the rewarding properties of nicotine, also regulate several central functions, such as memory and attention, sleep and wakefulness, anxiety and pain (19). The nAChRs have received little attention despite evidence that they play a role in the development of alcohol dependence.Studies have shown that the nonselective nAChR antagonist, mecamylamine, decreases ethanol consumption in rats (20)(21)(22) and attenuates ethanol-induced dopamine release in the nucleus accumbens (21,23,24). Furthermore, mecamylamine has been reported to block the stimulant or euphoric subjective effects of alcohol and decreases the self-reported desire to consume more alcohol in healthy human volunteers (25-27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This result raises the question of whether adolescents that coabuse tobacco and ethanol end up consuming more ethanol in order to attain the desired level of anxiolysis. In this regard, experimental studies in rodents have shown that nicotine increases ethanol self-administration and that this response is suppressed by the nicotinic antagonist mecamylamine (Le et al, 2000), which provides evidence for the involvement of nicotinic receptors in the modulation of ethanol consumption.…”
Section: Anxiolytic Effects During Adolescent Exposurementioning
confidence: 93%
“…In addition to metabolic cross-tolerance a variety of factors including genetic factors may contribute to the dependence on both nicotine and ethanol (Bierut et al, 2004;Goldman et al, 2005;Swan et al, 1997;True et al, 1999;Tyndale, 2003). Additionally, other physiological mechanisms could include the ability of nicotine and ethanol to induce dopamine release in the mesolimbic dopamine system, thereby potentiating each other's rewarding effects (Corrigall et al, 1994;Gonzales et al, 2004), as well as a possible role of activation of nicotinic acetylcholine receptors (Blomqvist et al, 1996;Le et al, 2000). Our study demonstrates that the higher levels of hepatic CYP2E1 after chronic nicotine pretreatment and ethanol self-administration were accompanied by an increase in ethanol consumption and it remains to be tested whether metabolic crosstolerance directly contributes to this.…”
Section: Discussionmentioning
confidence: 99%